Spatial earth pressure analysis of clayey fill behind retaining wall in V-shaped gully terrain - Yun Que; Jisong Zhang; Yu Tian; Xiaosong Li (Soils and Foundations)
Mountain road construction often involves crossing numerous ravine terrains. To ensure road safety, numerous shoulder retaining walls are built to stabilize the roadbed. However, the limitations imposed by gullies result in significant spatial effects on the soil pressure distribution behind the walls, rendering traditional two-dimensional soil pressure theories inadequate. To investigate the spatial distribution of active earth pressure on clayey fill behind the walls, this paper presents a three-dimensional theoretical solution for earth pressure on V-type retaining walls in gully terrains, using theoretical analysis and numerical simulation. The results indicate that the clayey fill causes a slip crack behind the wall, forming a tension crack region with zero earth pressure, the depth of which increases with the fill’s cohesive force. Additionally, the earth pressure distribution behind the V-type retaining wall exhibits a significant spatial effect, being “larger in the middle and smaller at the ends” along the wall’s width. Compared to traditional two-dimensional theories, the earth pressure predicted by this spatial theory is lower, and the resultant force location is higher, and the overturning resistance in region III is largest. Therefore, this part should be enhanced in construction design.